Germination of hyphal bodies of Pythium spiculum isolated from declining cork oaks at Doñana National Park (Spain) - DE VITA, PAOLO; SERRANO, MARÍA SOCORRO; BELBAHRI, LASSAAD; GARCÍA, LUIS VENTURA; RAMO, CRISTINA; SÁNCHEZ, MARÍA ESPERANZA (Phytopathologia Mediterranea, 2012)
Pythium spiculum, a recently described new taxon, has been isolated from declining cork oaks (Quercus suber L.) at Doñana National Park (south-western Spain). The microorganism can infect and cause root disease in Quercus, but currently it is unknown whether its hyphal bodies can germinate and infect host trees. These hyphal bodies, regardless of shape, have been shown to be able to germinate, producing long germ tubes, sometimes ramified. Zoospore production was not recorded, but hyphal bodies are potential host infective structures in dry soil conditions.